Anthropometric and fitness associations in U17 Italian football players - Nughes, E.; Aquino, R.; Ermidis, G.; Castorelli, V.; Raiola, G.; Rago, V. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The purpose of this study was to determine possible relationships between anthropometric characteristics and functional capacities in young football (soccer) players. METHODS: Anthropometric characteristics, estimated peak height velocity (PHV), muscular endurance (sit-up), lower-limb power (countermovement jump, CMJ), sprint time over 5 and 15 m (T5 and T15), agility (Arrowhead agility test), repeated sprint ability (RSA), intermittent recovery capacity (Yo-Yo intermittent recovery test, Yo-Yo IR1) and technical skills (short dribbling tests) were assessed in a group of U17 players (N.=47) competing at regional level. Magnitude-based inferences were used for analyses. RESULTS: Players with later PHV had greater muscle endurance (r [90% CIs] =0.41 [0.18; 0.59]) and CMJ (r=0.47 [0.25; 0.64]). Body mass, height and percentage of fat mass were positively associated to T5 and T15 (r=0.24-0.47). CMJ was moderately associated with agility, T5, T15 and Yo-Yo IR1 performance (r=-0.42 [-0.60; -0.19], -0.57 [-0.71; -0.38], 0.35[0.11; 0.54], respectively). Quickest players over 15 m were also the most agile and the most capable to perform intermittent recovery exercise (r=0.30-0.36). No significant correlations were found for RSA and other variables. CONCLUSIONS: Body size is likely detrimental for power-related capacities (tallest and heaviest players reported the lowest sprint performance). Notwithstanding, sprint and jump were related to greater intermittent recovery performance. However, caution should be taken when generalizing our findings, given our reduced sample size. In addition, our observed correlations were of small-to-moderate magnitude, and therefore, future research should explore further determinants of functional capacities in these age-group players.